Предмет: Химия,
автор: Красотка000
Записать развернутое, а затем сокращенное уравнение:
H2SiO3 разлагается на
ZnCL+KOH=
K2SiO3+HCL=
BaCL2+K2SO4=
CuSO4+Fe=
Ответы
Автор ответа:
0
H2SiO3=H2O+SiO2
ZnCl2+2KOH=Zn(OH)2+2KCl
Zn(2+)+2CL(-)+2K(+)+2OH(-)=Zn(OH)2+2K(+)+2Cl(-)
Zn(2+)+2OH(-)=Zn(OH)2
K2SiO3+2HCl=2KCl+H2SiO3
2K(+)+SiO3(2-)+2H(+)+2Cl(-)=2K(+)+2Cl(-)+H2SiO3
2H(+)+SiO3(2-)=H2SiO3
BaCl2+K2SO4=BaSO4+2KCl
Ba(2+)+2Cl(-)+2K(+)+SO4(2-)=BaSO4+2K(+)+2Cl(-)
Ba(2+)+SO4(2-)=BaSO4
CuSO4+Fe=FeSO4+Cu
Cu(2+)+SO4(2-)+Fe(0)=Fe(2+)+SO4(2-)+Cu(0)
Cu(2+)+Fe(0)=Fe(2+)+Cu(0)
ZnCl2+2KOH=Zn(OH)2+2KCl
Zn(2+)+2CL(-)+2K(+)+2OH(-)=Zn(OH)2+2K(+)+2Cl(-)
Zn(2+)+2OH(-)=Zn(OH)2
K2SiO3+2HCl=2KCl+H2SiO3
2K(+)+SiO3(2-)+2H(+)+2Cl(-)=2K(+)+2Cl(-)+H2SiO3
2H(+)+SiO3(2-)=H2SiO3
BaCl2+K2SO4=BaSO4+2KCl
Ba(2+)+2Cl(-)+2K(+)+SO4(2-)=BaSO4+2K(+)+2Cl(-)
Ba(2+)+SO4(2-)=BaSO4
CuSO4+Fe=FeSO4+Cu
Cu(2+)+SO4(2-)+Fe(0)=Fe(2+)+SO4(2-)+Cu(0)
Cu(2+)+Fe(0)=Fe(2+)+Cu(0)
Похожие вопросы
Предмет: Английский язык,
автор: akuskinakata142
Предмет: Русский язык,
автор: parencrut007
Предмет: Математика,
автор: BZHR
Предмет: Литература,
автор: нась4ка
Предмет: Биология,
автор: крэйда